Pengaruh Pemanfaatan Teknologi Informasi, Pengawasan, dan Kepuasan Kerja Terhadap Produktivitas Pegawai Dinas Pendidikan Kepemudaan dan Olah Raga Kabupaten Badung - Krishna, I Gusti Ngurah Agung Cahya; Sumada, I Made; Dewi, Nyoman Diah Utari (LPPM Institut Pendidikan Nusantara Global, 2024)
The Badung Regency Education, Youth, and Sports Office is important in providing education services, youth development, and managing sports activities in the region. Employee productivity is critical to an organization's success. With high productivity, organizations can achieve organizational goals and provide quality services. The purpose of this study was to examine how information technology utilization, supervision, and job satisfaction affect the work productivity of Badung Education, Youth, and Sports Office employees. The total sampling method resulted in 94 respondents. The questionnaire utilized a Likert scale for data collection. We employed multiple linear regression analysis techniques with SmartPLS for data analysis. The results showed that the use of information technology has a positive and significant effect on work productivity. Supervision has a positive and significant effect on work productivity. Information technology utilization, supervision, and job satisfaction have a significant effect on work productivity. We recommend providing employees with the necessary hardware and software to perform their duties effectively.